Konsep Penyajian Gandang Sarunai Di Nagari Luak Kapau Kabupaten Solok Selatan - Rezi Susanto (Institut Seni Indonesia Padang Panjang, 2021)
This paper discusses Gandang Sarunai, a type of traditional percussion art in South Solok. The goal is to describe the concept of its presentation. With a qualitative approach, observations were made on the practice of presenting Gandang Sarunai in Nagari Luak Kapau, South Solok, by departing from an ethnomusicological understanding. Research shows that the presentation of Gandang Sarunai has several unique features, namely: combining elements of rhythm with elements of melody; the position of the player in the presentation, with two players facing each other playing the same double; and the playing system, which begins with the gandang palalu rhythm pattern, followed by the gandang paningkah, and also followed by the Sarunai instrument which plays non-rhythmically with a free melody and is not bound by the grooves of the gandang rhythm pattern.Keywords: presentation; traditional percussion; Gandang Sarunai; South SolokAbstrakTulisan ini membahas tentang Gandang Sarunai, sebuah jenis kesenian perkusi tradisional di Solok Selatan. Tujuannya untuk menguraikan perihal konsep penyajian dari kesenian tersebut. Dengan pendekatan kualitatif, pengamatan dilakukan terhadap praktik penyajian Gandang Sarunai di nagari Luak Kapau, Solok Selatan, dengan berangkat dari pemahaman etnomusikologi. Penelitian menunjukkan bahwa penyajian Gandang Sarunai memiliki beberapa keunikan, yakni: memadukan antara unsur ritme dengan unsur melodi; posisi pemain dalam penyajian, dengan dua pemain berhadapan memainkan gandang yang sama; dan sistem permainan, yang diawali oleh permainan pola ritme gandang palalu, diikuti oleh gandang paningkah, dan diikuti pula oleh instrumen Sarunai yang bermain sacara non-ritmis dengan melodi bebas dan tidak terikat oleh alur dari jalinan pola ritme gandang.Kata Kunci: penyajian; perkusi tradisional; Gandang Sarunai; Solok Selatan